2022
DOI: 10.1001/jamaophthalmol.2021.5977
|View full text |Cite
|
Sign up to set email alerts
|

Serious Adverse Events of Oral and Topical Carbonic Anhydrase Inhibitors

Abstract: laucoma is a progressive optic neuropathy that affects more than 60 million patients worldwide. 1 Carbonic anhydrase inhibitors (CAIs) decrease aqueous humor production, thus lowering intraocular pressure. 2 Topical CAIs are associated with a 20% intraocular pressure reduction, whereas oral CAIs are associated with a 30% intraocular pressure reduction. 3,4 When there are concerns about efficacy or patient adherence, oral CAIs are sometimes preferred over topical agents.Topical CAIs are often prescribed early i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…In Reply We thank Bleicher et al for their comments. We found that carbonic anhydrase inhibitors have a low risk of severe adverse reactions regardless of whether prescribed as oral or topical formulations . Moreover, our study was designed in a manner slanted against this conclusion; namely, the risk of Stevens-Johnson syndrome, toxic epidermal necrolysis, or aplastic anemia could be even lower if estimated by different analytic methods.…”
mentioning
confidence: 87%
“…In Reply We thank Bleicher et al for their comments. We found that carbonic anhydrase inhibitors have a low risk of severe adverse reactions regardless of whether prescribed as oral or topical formulations . Moreover, our study was designed in a manner slanted against this conclusion; namely, the risk of Stevens-Johnson syndrome, toxic epidermal necrolysis, or aplastic anemia could be even lower if estimated by different analytic methods.…”
mentioning
confidence: 87%
“…The treatment of glaucoma requires a high dose of sulfonamide drugs to effectively reduce intraocular pressure. Those drugs have shown poor specificity for the targeted isozyme, therefore causing a wide range of undesirable side effects, including altered taste, malaise, fatigue, depression, and anorexia [ 25 , 26 ]. In addition, some of the marketed sulfonamide drugs cause allergies in a significant number of people [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…To the Editor We read with great interest the article by Popovic et al and we appreciate the opportunity to comment. The authors compare the risk of Stevens-Johnson syndrome/toxic epidermal necrolysis (SJS/TEN) and aplastic anemia after exposure with topical vs oral carbonic anhydrase inhibitors (CAIs).…”
mentioning
confidence: 99%
“…There are some potential contributors to a seemingly elevated rate. The authors did not report data on how representative the database is of the general population. What is the overall rate of SJS/TEN in their database?…”
mentioning
confidence: 99%
See 1 more Smart Citation